2023
DOI: 10.1007/s00018-023-04783-y
|View full text |Cite
|
Sign up to set email alerts
|

A structural model of the iRhom–ADAM17 sheddase complex reveals functional insights into its trafficking and activity

Abstract: Several membrane-anchored signal mediators such as cytokines (e.g. TNFα) and growth factors are proteolytically shed from the cell surface by the metalloproteinase ADAM17, which, thus, has an essential role in inflammatory and developmental processes. The membrane proteins iRhom1 and iRhom2 are instrumental for the transport of ADAM17 to the cell surface and its regulation. However, the structure–function determinants of the iRhom–ADAM17 complex are poorly understood. We used AI-based modelling to gain insight… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 102 publications
6
22
0
Order By: Relevance
“…As iRhom levels are a rate limiting factor for forward transport and maturation of ADAM17, increased expression of either human or murine wt-iRhom2 results in more mature ADAM17 (Fig. 3A-C), as shown before (Düsterhöft et al, 2021, Kahveci-Türköz et al, 2023. Consequently, the amount of mature ADAM17 on the cell surface is also elevated (Fig.…”
Section: Results Irhom2 Expression Levels Are High In Skin and Osccmentioning
confidence: 69%
See 4 more Smart Citations
“…As iRhom levels are a rate limiting factor for forward transport and maturation of ADAM17, increased expression of either human or murine wt-iRhom2 results in more mature ADAM17 (Fig. 3A-C), as shown before (Düsterhöft et al, 2021, Kahveci-Türköz et al, 2023. Consequently, the amount of mature ADAM17 on the cell surface is also elevated (Fig.…”
Section: Results Irhom2 Expression Levels Are High In Skin and Osccmentioning
confidence: 69%
“…7). During maturation, the proteolytic removal of the ADAM17 prodomain may further decrease binding affinity, as our recent study identified the prodomain as an additional binding determinant between the ADAM17 ectodomain and the IRHD (Kahveci-Türköz et al, 2023). The reduced cohesion of the iRhom2-matureADAM17 complex on the cell surface appears to induce instability and accelerated turnover, culminating in lysosomal degradation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations